2016
DOI: 10.2217/nmt-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Remediation to Enhance Mobility in Older Adults: the Crem Study

Abstract: Mobility disabilities represent the most prevalent disability among seniors. Emerging evidence indicates that executive functions play an important role in maintaining mobility. However, the use of cognitive remediation programs to enhance mobility has not been investigated in a full-scale randomized control trial. The CREM study is a single-blind randomized control trial to examine the effect of computerized cognitive remediation versus computer-based health education training on mobility in 420 seniors. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…8,11,12,17,2124 It is hypothesized that specialized cognitive training, with a strong emphasis on executive control training, will provide beneficial effects on gait and executive functions through its impact on this frontosubcortical circuit. 35 Frontosubcortical circuits link specific regions of the frontal cortex (namely, prefrontal cortex) to the basal ganglia (motor control). 36 That is, given its plastic properties, the brain is able to continuously change in response to engagement in repeated sensory, motor, and/or cognitive activities.…”
Section: Discussionmentioning
confidence: 99%
“…8,11,12,17,2124 It is hypothesized that specialized cognitive training, with a strong emphasis on executive control training, will provide beneficial effects on gait and executive functions through its impact on this frontosubcortical circuit. 35 Frontosubcortical circuits link specific regions of the frontal cortex (namely, prefrontal cortex) to the basal ganglia (motor control). 36 That is, given its plastic properties, the brain is able to continuously change in response to engagement in repeated sensory, motor, and/or cognitive activities.…”
Section: Discussionmentioning
confidence: 99%
“…CogniFit (CogniFit, San Francisco, CA, USA), a commercially available software, provides training across multiple cognitive domains, including executive functions and other related processes-such as speed of processing, divided attention, and visuospatial skills-that are relevant to walking performance. 3,11,18 Previous studies have suggested that training with CogniFit might improve walking speed. 3,12,18 For the intervention group, groups of up to eight participants attended three training days per week for 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…3,11,18 Previous studies have suggested that training with CogniFit might improve walking speed. 3,12,18 For the intervention group, groups of up to eight participants attended three training days per week for 8 weeks. Each session was about 50 min (150 min weekly) and was split into three blocks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations